Tomatoes or tomato pickers?: the NAFTA case - Melchor del Río, Amaranta; Thorwarth, Susanne (Discussion paper series, 2006)
This paper examines the relationship between trade liberalisation and migration in the case of Mexico. The increasing bilateral trade between Mexico and the United States after signing the North American Free Trade Agreement (NAFTA) was supposed to stem the illegal Mexican migration flow by contributing to economic growth and job creation in both countries. Twelve years after the treaty has come into effect questions emerge to what extent NAFTA was able to reduce the migration pressure: are trade and migration substitutes like the policy-makers had assumed or are they complements? Using monthly data from 1966 until 2004 we estimate a distributed lag model with the number of apprehensions at the US-Mexican border as a proxy for illegal migration. The results indicate that increasing trade flows cause larger illegal migration from Mexico to the United States.
Keywords: Amtsdruckschrift; Statistik; Arbeitspapier; Graue Literatur